1999
DOI: 10.1897/1551-5028(1999)018<2859:eoaptw>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Pulsed Treatment With the Herbicide Afalon (Active Ingredient Linuron) on Macrophyte-Dominated Mesocosms. I. Responses of Ecosystem Metabolism

Abstract: Abstract-Experimental drainage ditches used as mesocosms were treated with linuron three times, at 4-week intervals, at nominal concentrations of 0, 0.5, 5, 15, and 50 g/L. After each treatment, the mesocosms were kept static for 1 week. They were then flushed with noncontaminated surface water, with a residence time of 5 d, until the next treatment. Structural and functional measurements were made. A companion paper discusses the structural aspects. Dissolved oxygen concentrations and pH were measured continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Most mesocosm studies investigating effects of herbicides have shown a decrease of photosynthetic activity in combination with a decrease in dissolved oxygen as a result of their impact on macrophytes and phytoplankton (e.g., Kersting and Van Wijngaarden [16]). This indicates an increased photosynthetic activity on these days despite a decline in chlorophyll a concentration and phytoplankton abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Most mesocosm studies investigating effects of herbicides have shown a decrease of photosynthetic activity in combination with a decrease in dissolved oxygen as a result of their impact on macrophytes and phytoplankton (e.g., Kersting and Van Wijngaarden [16]). This indicates an increased photosynthetic activity on these days despite a decline in chlorophyll a concentration and phytoplankton abundance.…”
Section: Discussionmentioning
confidence: 99%
“…These expectations were based on results of a previous experiment with linuron [1,2]. However, expected direct effects can lead to less predictable indirect effects on, for example, the animal community [2,3]. We therefore studied flo‐ristic and faunal endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…The answer has been demonstrated to be conclusively no by Kersting and Van Wijngaarden [12] using a very different multispecies system. The answer has been demonstrated to be conclusively no by Kersting and Van Wijngaarden [12] using a very different multispecies system.…”
Section: Persistence Of Effectsmentioning
confidence: 99%
“…Kersting and Van Wijngaarden [12] and Van Geest et al [33] discuss the relative importance of these measures in a series of herbicide mesocosm experiments. Functional variables are those measures that describe the metabolism of an ecological system.…”
Section: Introductionmentioning
confidence: 99%